Descriptions of Philometra aenei n. sp. and P. tunisiensis n. sp. (Nematoda: Philometridae) from Epinephelus spp. off Tunisia confirm a high degree of host specificity of gonad-infecting species of Philometra Costa, 1845 in groupers (Serranidae) - Moravec, František; Chaabane, Amira; Neifar, Lassad; Gey, Delphine; Justine, Jean-Lou (Systematic parasitology, 2016)
Based on light and electron microscopical studies of males and mature females, two new gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) are described from the ovary of groupers, Epinephelus spp. (Perciformes; Serranidae), in the Mediterranean Sea off Tunisia (near Sfax): Philometra aenei n. sp. from the white grouper E. aeneus (Geoffroy Saint-Hilaire) and P. tunisiensis n. sp. from the goldblotch grouper E. costae (Steindachner). Identification of both fish hosts was confirmed by barcoding of the infected fish specimens. Philometra aenei is mainly characterised by the length of conspicuously distended spicules (108-123 µm), the presence of a distinct dorsal barb at the middle region of the gubernaculum and a distinct protuberance consisting of two dorsolateral lamellar parts separated from each other by a smooth median field at its distal tip, a V-shaped mound on the male caudal extremity and by the body length of the males (2.34-3.05 mm). The male of this species was found to possess minute deirids in the cervical region, which is quite exceptional within the Philometridae. Philometra tunisiensis is distinguished from other gonad-infecting congeneric species parasitising serranids by the length of the needle-like spicules and gubernaculum (201-219 and 78-87 µm, respectively), spicule length representing 9-11% of body length, the gubernaculum/spicules length ratio of 1:2.52-2.77, the length of oesophagus in the male comprising 15-16% of the body length, the absence of a dorsal protuberance on the distal lamellar part of the gubernaculum and a pair of large papillae posterior to the cloaca, a dorsally interrupted mound on the male caudal extremity and the body length of the male (2.01-2.42 mm). The presence of three morphologically very different species of Philometra in congeneric hosts in the Mediterranean Sea confirms a high degree of host specificity of these gonad-infecting nematodes parasitising groupers.
Keywords: Microscopy, Electron, Scanning; Dracunculoidea; mikroskopie elektronová rastrovací; mužské pohlaví; Středozemní moře; Tunisko; Gonads; gonády; ženské pohlaví; zvířata; Host Specificity; Species Specificity; Tunisia; Perciformes; druhová specificita; Female; Mediterranean Sea; hostitelská specificita; Male; Animals